Whole exome sequencing reveals genetic landscape associated with left ventricular outflow tract obstruction in Chinese Han population - Geng, Zilong; Li, Wenjuan; Yang, Ping; Zhang, Shasha; Wu, Shuo; Xiong, Junhao; Sun, Kun; Zhu, Dan; Chen, Sun; Zhang, Bing (Frontiers in Genetics, 2023)
Left ventricular outflow tract obstruction (LVOTO), a major form of outflow tract malformation, accounts for a substantial portion of congenital heart defects (CHDs). Unlike its prevalence, the genetic architecture of LVOTO remains largely unknown. To unveil the genetic mutations and risk genes potentially associated with LVOTO, we enrolled a cohort of 106 LVOTO patients and 100 healthy controls and performed a whole-exome sequencing (WES). 71,430 rare deleterious mutations were found in LVOTO patients. By using gene-based burden testing, we further found 32 candidate genes enriched in LVOTO patient including known pathological genes such as GATA5 and GATA6. Most variants of 32 risk genes occur simultaneously rather exclusively suggesting polygenic inherence of LVOTO and 14 genes out of 32 risk genes interact with previously discovered CHD genes. Single cell RNA-seq further revealed dynamic expressions of GATA5, GATA6, FOXD3 and MYO6 in endocardium and neural crest lineage indicating the mutations of these genes lead to LVOTO possibly through different lineages. These findings uncover the genetic architecture of LVOTO which advances the current understanding of LVOTO genetics.